Determinasi DETERMINASI MINAT BELI KONSUMEN MELALUI CITRA MEREK, HARGA, LOKASI, DAN PROMOSI PENJUALAN PADA FRESH ULU PALEMBANG - M Nanda Wijaya; Herry widagdo (Universitas Multi Data Palembang, 2026)
This study aims to analyze the influence of Brand Image, Pricing, Location, and Sales Promotion on Purchase Intention at Fresh Ulu Palembang. The research method used was quantitative with a descriptive approach. Data were obtained through questionnaires distributed to the public in Palembang. Data analysis was performed using IBM SPSS Statistics 25 through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis tests, and coefficient of determination tests. The results indicate that Brand Image, Pricing, Location, and Sales Promotion have a significant effect, both partially and simultaneously, on Fresh Ulu Palembang. The implications of this study are expected to provide considerations for companies in formulating strategies to improve Brand Image, Pricing, Location, and Sales Promotion on purchase intention at Fresh Ulu Palembang on a sustainable basis.